Efektivitas Penggunaan Aplikasi Elsimil dan Video YouTube terhadap Tingkat Pengetahuan Calon Pengantin tentang Stunting - Syafril, Asrizul; Arif, Ernita; Asmawi, Asmawi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
One effort to reduce the incidence of stunting is through Communication, Information, and Education to prospective newlyweds through media such as the Elsimil application and YouTube videos. The use of media is expected to make communication more effective, so that the information about stunting conveyed can be well understood by prospective newlyweds. The aim of this study is to determine the effectiveness of using the Elsimil application, YouTube video media, and the combination of Elsimil application plus YouTube video on improving the knowledge of prospective newlyweds about stunting. This study used a one-group pretest-posttest design on three groups of respondents. The number of respondents in each group was 10 people, making a total sample of 30 people. Data collection was conducted through pretest and posttest questionnaires for each group at the Office of Religious Affairs (KUA) of Lengayang Sub-district from August 2023 to September 2023. The data analysis used was paired t-test. The results showed a significant difference in the level of knowledge of prospective newlyweds before and after being treated using each media: Elsimil application, YouTube video, and combination of Elsimil application plus YouTube video. The use of the combination of Elsimil application plus YouTube video media provides more effective results in improving the knowledge of prospective newlyweds about stunting compared to other media.